Research hotspots and frotiers of stem cells in stroke: A bibliometric analysis from 2004 to 2022 - Zhang, Qi; Zeng, Yuting; Zheng, Shuqi; Chen, Ling; Liu, Haining; Chen, Hui; Zhang, Xiaofeng; Zou, Jihua; Zheng, Xiaoyan; Wan, Yantong; Huang, Guozhi; Zeng, Qing (Frontiers in Pharmacology, 2023)
Background: Stroke is one of the leading causes of mortality and permanent disability worldwide. However, the current stroke treatment has a limited effect. Therefore, a new treatment is urgently needed. Stem cell therapy is a cutting-edge treatment for stroke patients. This study aimed to gain better understanding of global stem cell trends in stroke via a bibliometric analysis. Methods: We used the Web of Science Core Collection to search pertinent articles about stem cells in stroke published between 2004 and 2022. Analysis was conducted using CiteSpace, VOSviewer, and the R package “bibliometrix” to identify publication outputs, countries/regions, institutions, authors/co-cited authors, journals/co-cited journals, co-cited references, and keywords. Results: A total of 6,703 publications were included in the bibliometric analysis. The total number of citations significantly and rapidly increased between 2004 and 2022, with the most pronounced growth pattern observed in the period of 2008–2009. In terms of authoritarian countries, the USA had the most publications among the countries. As for institutions and authors, the most prolific institution was the University of South Florida, followed by Oakland University and then Shanghai Jiao Tong University, and Chopp, M., and Borlongan, Cesario V, had the most output among the authors. Regarding the journals, Cell Transplantation had the highest publication, followed by Brain Research. As for references, “Mesenchymal stem cells as trophic mediators” was the most frequently cited (2,082), and the article entitled Neuronal replacement from endogenous precursors in the adult brain after stroke had the strongest burstiness (strength = 81.35). Emerging hot words in the past decade included “adhesion molecule,” “mesenchymal stromal cell,” “extracellular vesicle,” “pluripotent stem cells,” “signaling pathway,” “plasticity,” and “exosomes.” Conclusion: Between 2004 and 2022, the terms “neurogenesis,” “angiogenesis,” “mesenchymal stem cells,” “extracellular vesicle,” “exosomes,” “inflammation,” and “oxidative stress” have emerged as the hot research areas for research on stem cells in stroke. Although stem cells exert a number of positive effects, the main mechanisms for mitigating the damage caused by stroke are still unknown. Clinical challenges may include complicating factors that can affect the efficacy of stem cell therapy, which are worth a deep exploration.